Contending with Gun Violence - Katie Sluiter (University of Oklahoma Libraries, 2020)
Katie Sluiter interviews three English Education Professors: Steven Bickmore, Shelly Shaffer, and Gretchen Rumhor. The conversation centers on their scholarship in the field of Young Adult Literature, as well as their book, Contending with Gun Violence in the English Language Classroom.